1999
DOI: 10.1136/hrt.81.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of losartan improve the beneficial effects of ACE inhibitors in patients with anterior myocardial infarction? A pilot study

Abstract: Conclusion-The data suggest that the combination of captopril plus losartan is feasible in the early treatment of acute myocardial infarction patients, and it appears that this combination has more eVect on ESV than captopril alone in the short term. (Heart 1999;81:606-611)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…An older randomized trial showed a reduction in mortality with an increased risk of hypotension in patients treated soon after presentation in the inpatient setting. 183 Several trials showed a reduction in the rate of heart failure and mortality in patients treated soon after fibrinolysis, [363][364][365] and several others showed no benefit with the early or prehospital use of angiotensin converting enzyme. 364,366,367 In conclusion, although ACE inhibitors and ARBs have been shown to reduce long-term risk of mortality in patients suffering an AMI, there is insufficient evidence to support the routine initiation of ACE inhibitors and ARBs in the prehospital or ED setting (Class IIb, LOE C).…”
Section: Ace Inhibitors In the Prehospital Settingmentioning
confidence: 99%
“…An older randomized trial showed a reduction in mortality with an increased risk of hypotension in patients treated soon after presentation in the inpatient setting. 183 Several trials showed a reduction in the rate of heart failure and mortality in patients treated soon after fibrinolysis, [363][364][365] and several others showed no benefit with the early or prehospital use of angiotensin converting enzyme. 364,366,367 In conclusion, although ACE inhibitors and ARBs have been shown to reduce long-term risk of mortality in patients suffering an AMI, there is insufficient evidence to support the routine initiation of ACE inhibitors and ARBs in the prehospital or ED setting (Class IIb, LOE C).…”
Section: Ace Inhibitors In the Prehospital Settingmentioning
confidence: 99%
“…The primary search for clinical trials on MRAs and left ventricular dysfunction generated 559 potentially relevant articles, of which 19 met the selection criteria and were published between 1995 and 2011. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A flow diagram schematized the process of selecting and excluding articles with specific reasons (Figure 1). Five of 19 qualified trials recorded outcomes within >1 time point in treatment, yielding a total of 26 studies conducted exclusively in subgroup analyses by treatment durations.…”
Section: Eligible Trialsmentioning
confidence: 99%
“…In the case of ARBs and MI risk, one would expect to observe an In our inclusive, systematic review of 25 trials, [13][14][15][16][17][18][19][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]53,[55][56][57] 68 711 patients at risk for MI, and Ͼ4000 events, we now have even stronger evidence that ARBs do not increase the risk of MI, with a pooled OR of 1.03 (95% CI 0.93 to 1.13). Although few of these studies were designed to test equivalence, with a point estimate very close to unity and narrow CIs, it is clear that there is no increased risk of MI associated with ARB use.…”
Section: Do Arbs Increase the Risk Of Mi?mentioning
confidence: 99%